Perancangan Visual display Dalam Meningkatkan Disiplin Operator : Studi Kasus: PT. Baja Kurnia - Mauluddin, Yusuf; Hidayatullah, Anung Andi; Ismail, Saep (Jurnal Kalibrasi, 2025)
This study aims to improve operator discipline in the use of Personal Protective Equipment (PPE) at PT. Baja Kurnia through a participatory ergonomics approach. Quantitative methods were used, involving 48 operators, division heads, and an ergonomics expert in the process of identifying problems and implementing solutions. Based on the hazard and operability study (HAZOP) analysis, 13 potential extreme risks were identified, with the main causes being low knowledge and attitude towards PPE (52.9% each). A visual display design was chosen as the solution because it was easy to understand and feasible to implement. Validation of the solution showed a 29.4% increase in knowledge and a 17.6% increase in positive attitudes toward PPE. These results indicate that visual displays are effective in improving operator work discipline. The practical implication of this study is that visual displays can be part of occupational safety strategies in the manufacturing sector, particularly in strengthening a culture of discipline and accident prevention.